Political Reform in Saudi Arabia: Necessity or Luxury? - Albassam, Bassam A. (Mediterranean Journal of Social Sciences, 2011)
Since its founding in 1932, the Kingdom of Saudi Arabia has never had a written constitution or any form of publicparticipation in the policy process and governmental decision-making process. Since 1992, the rulers have been under increasing pressureto formulate a written constitution and to increase public participation in the policy process. As a response, Saudi rulers have enactedmany laws, which they claimed were a new constitution for the country. This paper argues that the reforms introduced in Saudi Arabiaare empty reforms that put the country’s political stability in jeopardy. In contrast, increasing public participation in the policy process willensure political stability and legitimize rulers’ authority. Thus, without political reform that guarantees citizen participation in the policyand governmental decision-making processes, the country’s political future will continue to be controlled by a small group of people (theroyal family) who often disagree amongst themselves about what is best for the country.